IMPROVING FINANCIAL LITERACY IN MSMES THROUGH BOOKKEEPING TRAINING AND LITERACY EDUCATION - Hakima Maris; Ratih Kusumastuti; Muthmainah Mursidin; Hendra Railis; Dada Suhaida; Yuliana Yuliana (Yayasan Education and Social Center, 2022)
MSMEs are expected to be the forefront to strengthen economic pillars in achieving sustainable development goals (SGDs). This is because MSMEs are one of the most able businesses to survive in deteriorating economic conditions, especially in this Covid-19 pandemic. Therefore , MSMEs must have good financial management so that the business carried out can be sustainable. One of them is by having the correct financial record and compiling the financial statements needed to make decisions in planning the next business strategy. Food MSMEs in Indonesia do not have a good record, so they cannot produce financial statements. The results of training and mentoring make simple bookkeeping and compile these financial statements increase the awareness of MSME actors for the importance of information generated by financial statements. as the basis for decision making and preparing business strategies to achieve sustainable business